Can a molecular switch exist in both superalkali electride and superalkalide forms?. Issue 9 (21st February 2022) - Yi, Xiu-Guang; Wang, Yin-Feng; Zhang, Hua-Rong; Cai, Jin-Hua; Liu, Xue-Xia; Li, Jia; Wang, Zhi-Jun; Bai, Fu-Quan; Li, Zhi-Ru
Abstract : The superalkali electride e − ⋯Li3 + –PHY and superalkalide Li δ − –Li2 (1– δ )− –PHY − show a good switchable effect. Abstract : To combine both electride and alkalide characteristics in one molecular switch, it is shown herein that the phenalenyl radical and the M3 ring (M3 –PHY, M = Li, Na, and K) stacked with parallel and vertical geometries are good candidates. The former geometry is the superalkali electride e − ⋯M3 + –PHY while the latter geometry is the superalkalide M δ − –M2 (1– δ )+ –PHY − . The superalkalide M δ − –M2 (1− δ )+ –PHY − may isomerize to the superalkali electride e − ⋯M3 + –PHY (M = Li, Na, and K) using suitable long-wavelength irradiation, while the latter may isomerize to the former with suitable short-wavelength irradiation. Also, applying suitable oriented external electric fields can drive the superalkalide M δ − M2 (1− δ )+ –PHY − to change into the superalkali electride e − ⋯M3 + –PHY (M = Li, Na, and K). The differences in the static and dynamic first hyperpolarizability ( β 0 ) values between them were also studied.